Pendampingan Guru SD dalam Implementasi Pembelajaran Bahasa Indonesia Berbasis Proyek Literasi di SDN Bama 3 - Yoma Hatima; Rina Yuliana; Sigit Setiawan (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
The implementation of the Merdeka Curriculum emphasizes the importance of contextual and project-based learning, including in Indonesian language learning at the elementary school level. However, the reality in the field shows that many teachers still have difficulty in implementing this approach optimally. This community service activity aims to provide assistance to teachers at SDN Bama 3 so that they are able to design and implement Indonesian language learning based on literacy projects effectively and in accordance with the characteristics of students. The method of implementing the activity consists of initial observation, intensive training, learning simulations, and direct assistance in planning and implementing literacy projects in the classroom. The results of this activity show an increase in teachers' understanding of the concept of project-based learning, the ability to design literacy-based teaching tools, and high enthusiasm in integrating creative reading and writing activities into Indonesian language learning. Students also showed more active involvement and interest in literacy activities. Thus, this assistance makes a positive contribution to improving the quality of Indonesian language learning at SDN Bama 3. In the future, similar programs can be expanded to other schools to strengthen a culture of literacy from an early age.